THE EFFECT OF TIME TOKEN LEARNING MODEL ON STUDENTS CRITICAL ABILITY IN SOCIAL STUDIES (GEOGRAPHY) (Universitas Negeri Semarang, 2018)
Social Studies (Geography) learning still seems to have not achieved minimal completeness, among others, due to students learning less active. The method used in this study is the experimental method with Posttest only control design. The technique of collecting data is in the form of tests and documentation. Data analysis using normality test, homogeneity test and hypothesis test. The results of this study indicate that the experimental class treated with the time token learning model has an average value of 81.5 higher than the average of the control class treated with the lecture model getting a value of 63.81. This can be concluded that the time token learning model can improve critical thinking skills and the results of calculations on the T-test show that tcount> t table. where t count = 10.25 and t table = 1.67203. It means